Poetricks a game to engage Malaysian secondary school ESL learners in understanding poetry / Angeline Ranjethamoney Vijayarajoo ... [et al.] - Vijayarajoo, Angeline Ranjethamoney; Anuar Yatim, Ariff Imran; Maktiar Singh, Kuldip Kaur; Mohd Jani, Roslina (Penerbit UiTM (UiTM Press), 2019)
Studying literature can be challenging for ESL learners. With the new cycle of poems introduced by the Ministry of Education in 2015, the teachers responded with great concerns over how to teach their students, who found poetry difficult and boring. Furthermore, the teachers found poetry less favourable compared to other literary genres. In order to fill the gap of a better understanding of the poems, in more engaging ways, the researchers designed a board game. The compulsory (new) poems for Forms Four and Five were used. 20 students and 40 teachers participated in this study. Data comprised the responses of the students and teachers, to the questionnaire and interview after the game. The game sessions were videotaped. The analysis of the data showed that the participants responded positively to the game. Hence, this game served as a supplementary tool in the teaching and learning of poetry in more engaging ways.